Pathways to financial fiteracy: Exploring behaviors, information sources, and library usage hindrances among off-campus university student - Adetayo, Adebowale; Oyeniyi, Wosilat; Salvador, Mutiat; Adekunmisi, Sowemimo (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2023)
Background of the study: This study explores financial behaviors and information sources among off-campus university students, emphasizing challenges in using library materials for financial literacy. Purpose: The research aims to comprehensively understand the financial landscape of off-campus university students, identifying key behaviors, information sources, and obstacles related to financial literacy. Method: A cross-sectional survey involving 245 off-campus university students was conducted to gather pertinent data. A self-administered questionnaire served as the primary data collection tool. The collected data underwent analysis using descriptive statistics to draw meaningful insights. Findings: Off-campus university students' major expenses included school-related costs and food. Common financial behaviors included living within means, avoiding borrowing, and budgeting. Despite these practices, many students expressed financial dissatisfaction. Family members were the primary information source, followed by friends, Google, and online books. Libraries were not a significant source. Limited time emerged as the main hindrance to using library materials for financial literacy. Conclusion: In conclusion, off-campus university students, constrained by limited time, face challenges accessing library resources for financial literacy, necessitating targeted programs to address their unique needs and providing valuable insights for institutions and policymakers.